2019
DOI: 10.1080/20013078.2019.1632099
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Escherichia coli extracellular vesicle proteome identifies markers of purity and culture conditions

Abstract: Bacteria release nano-sized extracellular vesicles (EVs) into the extracellular milieu. Bacterial EVs contain molecular cargo originating from the parent bacterium and have important roles in bacterial survival and pathogenesis. Using 8-plex iTRAQ approaches, we profiled the EV proteome of two Escherichia coli strains, uropathogenic (UPEC) 536 and probiotic Nissle 1917. For these strains, we compared the proteome of crude input EVs prepared by ultracentrifugation alone with EVs purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 65 publications
7
88
0
Order By: Relevance
“…In nature, transformation, transduction, and conjugation are the principal mechanisms of HGT. Other mechanisms involve gene transfer agents (GTAs), nanotubes, and membrane vesicles (MVs) [which are also called extracellular vesicles (EVs) or exosomes] (Figure 1; Dauros Singorenko et al, 2017;Hong et al, 2019). Accordingly, the production of recombinant DNA can be achieved by directly transforming DNA or RNA from a donor, and subsequent integrating of foreign genetic material into the recipient cell's genome.…”
Section: Causes (Mediators) Of Hgt Hgt Mechanisms In Prokaryotesmentioning
confidence: 99%
“…In nature, transformation, transduction, and conjugation are the principal mechanisms of HGT. Other mechanisms involve gene transfer agents (GTAs), nanotubes, and membrane vesicles (MVs) [which are also called extracellular vesicles (EVs) or exosomes] (Figure 1; Dauros Singorenko et al, 2017;Hong et al, 2019). Accordingly, the production of recombinant DNA can be achieved by directly transforming DNA or RNA from a donor, and subsequent integrating of foreign genetic material into the recipient cell's genome.…”
Section: Causes (Mediators) Of Hgt Hgt Mechanisms In Prokaryotesmentioning
confidence: 99%
“…Also, EVs from probiotic bacteria have comparable effects to whole bacteria, increasing the number of T reg cells, in case of L. rhamnosus JB-1 9 , and promoting the survival of Caenorhabditis elegans exposed to vancomycin-resistant E. faecium by L. plantarum WCFS1 10 . Analysis of EVs from probiotic lactobacilli, like Lactobacillus rhamnosus , L. plantarum , L. reuteri and L. casei , showed that they contained glycolytic enzymes, chaperonins 9 , 11 – 14 and ligase functions 15 . In addition to proteins and membrane phospholipids, EVs from Gram-positive bacteria also contain lipoteichoic acid (LTA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while the quantity of EVs produced by extraintestinal pathogenic E. coli is not affected by iron starvation, changes in the EV proteome reflect a stressed cellular state (Chan et al, 2017). Finally, we have seen that iron-replete conditions cause UPEC EVs to be enriched in outer membrane components, while low iron conditions caused no enrichment, suggesting evidence of two different EV biogenesis mechanisms or differential packaging dependent on iron availability (Hong et al, 2019).…”
Section: Introductionmentioning
confidence: 72%
“…Our previous investigations into proteome of EVs showed that UPEC 536 EVs are enriched in rRNA-binding proteins in contrast to Nissle EVs, which are enriched in proteins involved in glycolytic process and ligase activity, leading us to believe that differential packaging of RNA may be causing some of the differences seen between UPEC and Nissle EV-RNA (Hong et al, 2019). A key investigation of this study was to delineate the effects of E. coli EV-RNA on host cell responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation